Improving regional universal newborn hearing screening programmes in Italy. - Molini, E; Cristi, M C; Lapenna, R; Calzolaro, L; Muzzi, E; Ciciriello, E; Della Volpe, A; Orzan, E; Ricci, G (Acta Otorhinolaryngol Ital, 2016)
The Universal Newborn Hearing Screening (UNHS) programme aims at achieving early detection of hearing impairment. Subsequent diagnosis and intervention should follow promptly. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", the limitations and strengths of current UNHS programs in Italy have been analysed by a group of professionals working in tertiary centres involved in regional UNHS programmes, using SWOT analysis and a subsequent TOWS matrix. Coverage and lost-to-follow up rates are issues related to UNHS programmes. Recommendations to improve the effectiveness of the UNHS programme have been identified. The need for homogeneous policies, high-quality information and dissemination of knowledge for operators and families of hearing-impaired children emerged from the discussion.